PORTABLE WIND TURBINES USES BLADE TYPE INVERSE TAPER - Dwi Lestariningtiyas; Basuki Winarno; Yuli Prasetyo (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2019)
The electrical energy is greatly needed in human’s life and even in the primary life of Indonesian. One of the renewable electrical energy resources is the wind energy which can be obtained by constructing a Wind Power Plant (PLTB, Pembangkit Listrik Tenaga Bayu). PLTB works by conversing the wind energy into electrical energy. PLTB that has been applied in Indonesia is using a permanent system with various kinds of blades. In this study, the Portable Wind Turbine is designed by using the inversed taper type blade. The Portable Wind Turbine consists of the inverse taper type wind turbine, DC dynamo, control circuit, and battery. The design begins with creating a simulation to design the turbine and control circuit. The turbine design uses Qblade and SolidWorks software for students, while the control circuit uses free version of Proteus software. The design result is a prototype which possesses a blade with 15cm and 8cm radius. The prototype testing is carried out by comparing two types of blade using various speed of artificial wind. The blade with 15cm length indicates a better result compared to the blade with 8cm. It produces a maximum voltage with the wind speed of 7m/s with 4,35volt and the current of 1,3 ampere.DOI : https://doi.org/10.26905/jeemecs.v2i2.3162